2015
DOI: 10.1186/s13229-015-0007-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine and behavioral response to social rupture and repair in preschoolers with autism spectrum disorders interacting with mother and father

Abstract: Background: Preschoolers with autism spectrum disorder (ASD) exhibit difficulties in handling social stress and utilizing efficient emotion regulation (ER) strategies to manage high arousal. While researchers called to assess ER in ASD, few studies utilized direct observations. We tested children's behavioral and cortisol response to maternal and paternal unavailability and hypothesized that children with ASD will employ less complex ER strategies and their parents would show increased regulation facilitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 64 publications
1
26
0
3
Order By: Relevance
“…These networks enable humans to share intentions and experiences during online social interactions (Frith and Frith, 2012) and their functioning has been shown to motivate empathic-related prosocial behavior in everyday life (Rameson et al , 2011). Preschoolers of parents with greater embodied-simulation connectivity displayed lower negative emotionality, which has been linked with greater social competence (Eisenberg et al , 2000), and greater use of complex regulatory strategies, abilities that characterize children with advanced social skills and lower psychopathology (Hirschler-Guttenberg et al , 2015; Ostfeld-Etzion et al 2015). Finally, preschoolers of parents who displayed higher connectivity of the mentalizing network exhibited higher self-regulated socialization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These networks enable humans to share intentions and experiences during online social interactions (Frith and Frith, 2012) and their functioning has been shown to motivate empathic-related prosocial behavior in everyday life (Rameson et al , 2011). Preschoolers of parents with greater embodied-simulation connectivity displayed lower negative emotionality, which has been linked with greater social competence (Eisenberg et al , 2000), and greater use of complex regulatory strategies, abilities that characterize children with advanced social skills and lower psychopathology (Hirschler-Guttenberg et al , 2015; Ostfeld-Etzion et al 2015). Finally, preschoolers of parents who displayed higher connectivity of the mentalizing network exhibited higher self-regulated socialization.…”
Section: Discussionmentioning
confidence: 99%
“…The Masks and Bubbles paradigms, tapping child emotion regulation, were each micro-coded for the child’s expression of positive emotionality (positive affect, positive vocalizations and laughter) and negative emotionality (negative affect, withdrawal, crying/yelling and protest). Two types of regulatory behaviors were micro-coded, consistent with prior research (Feldman et al, 2011; Hirschler-Guttenberg et al , 2015; Ostfeld-Etzion et al , 2015): Simple regulatory behaviors—included behaviors aiming solely at self-regulation that clearly display the child’s regulatory effort, such as physical self-soothing (e.g. thumb-sucking), verbal self-soothing (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the use of more complex and ecologically valid paradigms is likely to help tap into those processes that underlie social dysfunction in everyday-life social interactions. With regard to emotional regulation, for instance, it can be argued that emotion regulation in ontogeny is primarily an interpersonally constituted process, which may rely on parental abilities of social buffering [57]. Only later in life do children fully develop the capacity to independently regulate their own emotions.…”
Section: Introduction: Psychiatric Disorders As Disorders Of Social Imentioning
confidence: 99%
“…The result further indicated that each parenting style made a unique impact on social engagement in infants at high-and low-risk for ASDs. Ostfeld-Etzion, Golan, Hirschler-Guttenberg, Zagoory-Sharon, and Feldman, (2015) found that maternal presence and regulation facilitation provided social buffering for the children with ASDs' hypothalamic-pituitary-adrenal (HPA) stress response like mammalian neonates. This implied that poor social behaviour in high-risk infants as opposed to complex social behaviours of gestures and language may be masked through maternal behaviour.…”
Section: The Role Of the Parents In Building Resilience In Children Wmentioning
confidence: 99%